2020
DOI: 10.1038/s41598-020-58973-w
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism and anxiety may contribute to metabolic syndrome in Sichuan of China: a hospital-based population study

Abstract: the prevalence of Metabolic syndrome (MetS) in Sichuan of china has not yet been estimated. Meanwhile the association among anxiety, subclinical hypothyroidism (SCH) and MetS was less wellstudied. The data was retrieved retrospectively from Health Promotion Center of West China Hospital database between 2014 and 2017. Internal validation by randomizing into training and testing panel by 9:1 and external validation with National Health and Nutrition Examination Survey (NHNES) were conducted. 19006 subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
11
3
Order By: Relevance
“…However, after controlling for age and marital status, we found that they were not independent risk factors for MetS in AMD patients. This is inconsistent with previous studies, including several that have found that anxiety is a risk factor for MetS 18 , 42 . Other studies have also found that depression and anxiety further increase the risk of T2DM and cardiovascular events 43 , 44 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, after controlling for age and marital status, we found that they were not independent risk factors for MetS in AMD patients. This is inconsistent with previous studies, including several that have found that anxiety is a risk factor for MetS 18 , 42 . Other studies have also found that depression and anxiety further increase the risk of T2DM and cardiovascular events 43 , 44 .…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding psychotic symptoms, previous studies have demonstrated the potential interactions between psychotic symptoms and MetS 18 , 53 . Our study also found that compared with those with no psychiatric symptoms, AMD patients with psychiatric symptoms had a nearly twofold increased risk of MetS (OR 1.728, 95% CI 1.049–2.848), indicating that psychiatric symptoms may further increase the risk of MetS in AMD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of R. Li et al (2020), a multivariate analysis conducted among patients in China identified SH as an independent risk factor for the development of MS [18]. Interestingly, the multivariate logistic regression analysis performed by L. Jiang et al (2020), demonstrated the opposite impact, namely BMI and BP were independent predictors of SH development in women [19].…”
Section: Discussionmentioning
confidence: 99%
“…This is a population-based cross-sectional study among subjects undergoing routine health examinations at our hospital’s health management center from November 2018 to August 2019. The West China Hospital, a tertiary hospital with three subcenters in Sichuan, provides over 60,000 routine physical examinations annually ( 21 , 22 ). Participants were enrolled into the study if they fulfilled the following inclusion criteria: voluntarily go to the Health Management Center of West China Hospital of Sichuan University for health examination between November 2018 and August 2019; aged over 18 years; willing to sign an informed consent form.…”
Section: Methodsmentioning
confidence: 99%